1996
DOI: 10.1007/bf01411256
|View full text |Cite
|
Sign up to set email alerts
|

The surgical treatment of Chiari I malformation

Abstract: A retrospective study was undertaken on 133 patients with a Chiari I malformation treated within the last 16 years at the Departments of Neurosurgery at the Nordstadt Hospital Hannover, Germany, and the University of California, Los Angeles, U.S.A. Ninety-seven patients presented with symptoms related to accompanying syringomyelia and 4 with associated syringobulbia. They underwent 149 surgical procedures and were followed for a mean of 39 +/- 52 months. A decompression at the foramen magnum was performed in 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
92
1
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(102 citation statements)
references
References 54 publications
4
92
1
5
Order By: Relevance
“…1,3,4,[7][8][9][10][11]20,22,27 The PFD procedure alone, which is the standard treatment for CM-I, is considered inadequate in a small subgroup in which the risk of postoperative instability at the CCJ requires stabilization by a fixation procedure. 2,6,8,11,12,15 However, few large-scale studies have reported in detail the indications for treating such combined anomalies of the CCJ, and these entities are often the topic of isolated, smaller studies. Furthermore, the presence of concomitant CCJ bone anomalies with CM-I and/or syringohydromyelia is the subject of only a few case reports, with different treatment plans and choices for dorsal fusion.…”
Section: Discussionmentioning
confidence: 99%
“…1,3,4,[7][8][9][10][11]20,22,27 The PFD procedure alone, which is the standard treatment for CM-I, is considered inadequate in a small subgroup in which the risk of postoperative instability at the CCJ requires stabilization by a fixation procedure. 2,6,8,11,12,15 However, few large-scale studies have reported in detail the indications for treating such combined anomalies of the CCJ, and these entities are often the topic of isolated, smaller studies. Furthermore, the presence of concomitant CCJ bone anomalies with CM-I and/or syringohydromyelia is the subject of only a few case reports, with different treatment plans and choices for dorsal fusion.…”
Section: Discussionmentioning
confidence: 99%
“…4,[7][8][9] It involves removing bone in the suboccipital area along with the posterior margin of the foramen magnum Group I D A 128 66 37 20 5 Group II D+SS B 39 20 11 6 2 Group III D+T C 106 55 31 16 4 Group IV D+T+SS D 43 22 13 7 1 Abbreviations: CMI, Chiari I malformation; D, suboccipital decompression; MRI, magnetic resonance imaging; SS, syringosubarachnoid shunt; T, cerebellar tonsillectomy. Figure 1 Preoperative MRI scan of a patient with syringomyelia associated with CMI illustrating a prominent syrinx (arrow).…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have concluded that surgical treatment results in the improvement or stabilization of the disease in the majority of patients. 8,15 José Dones and De Jesú s 16 found that the main benefit of surgical treatment in patients with Chiari I malformation is to arrest the progression of symptoms. This pattern is not so clearly recognizable in our results, probably due to the small number of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Combined series, which included both pediatric and adult patients, constituted 61 reports (42%). [5][6][7]9,11,12,[25][26][27]34,37,38,40,43,44,46,47,52,53,55,63,66,67,70,73,74,76,83,87,90,91,94,96,100,102,103,106,110,111,114,115,117,121,126,127,129,130,132,135,[138][139][140]…”
Section: General Informationmentioning
confidence: 99%